Olive Cake in Calves Alimentation - ΕΥΣΤΑΘΙΟΥ Λ.; ΠΑΠΑΔΟΠΟΥΛΟΣ Π.; ΜΙΧΕΛΙΔΑΚΗΣ Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
1. The annual production of ordinary olive cake in Greece is about 300-400.000 tons and after its treatment in olive-Kernel factories 200.000 tons of exausted olive cake are obtained. 2. The chemical compositions of these products in referred in table I for the ordinary olive cake and table II for the exausted one with or without wooden pieces. 3. The administration to calves of exausted cake in a high percentage of 40-50% in mixtures with addition of molasses and carod bean pulp (20%), urea to 1% and other equilibrating substances gave satisfactory results. 554 calves of different origin, with an initial age of 5-8 months and an initial of 132+ 21 kg. after receiving the above mixture for 350+30 days at libertum they reached 421+41 kg. 4. No other crude food was given this mixture. The daily increase of the live weight was 825 g and there were not health problems. 5. Experiments are going on to improve the nutritive value of olive cake by adding caustic soda, standardizing it in pellets and observing the influence on yield and health of animals.